Measurement of Deformations by MEMS Arrays, Verified at Sub-millimetre Level Using Robotic Total Stations - Tomas Beran; Lee Danisch; Adam Chrzanowski; Maciej Bazanowski (Geoinformatics FCE CTU, 2014)
Measurement of sub-millimetre-level deformations of structures in the presence of ambienttemperature changes can be challenging. This paper describes the measurement of astructure moving due to temperature changes, using two ShapeAccelArray (SAA)instruments, and verified by a geodetic monitoring system. SAA is a geotechnicalinstrument often used for monitoring of displacements in soil. SAA uses micro-electro-mechanical system (MEMS) sensors to measure tilt in the gravity field. The geodeticmonitoring system, which uses ALERT software, senses the displacements of targetsrelative to control points, using a robotic total station (RTS). The test setup consists of acentral four-metre free-standing steel tube with other steel tubes welded to most of itslength. The central tube is anchored in a concrete foundation. This composite “pole” isequipped with two SAAs as well as three geodetic prisms mounted on the top, in the middle,and in the foundation. The geodetic system uses multiple control targets mounted inconcrete foundations of nearby buildings, and at the base of the pole. Long-termobservations using two SAAs indicate that the pole is subject to deformations due to cyclicalambient temperature variations causing the pole to move by a few millimetres each day. Ina multiple-day experiment, it was possible to track this movement using SAA as well as theRTS system. This paper presents data comparing the measurements of the two instrumentsand provides a good example of the detection of two-dimensional movements of seeminglyrigid objects due to temperature changes.